(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Epicycloid hypoid gear in the rear driving axle main reducer in the process of skid gear is often a wide range of failures occur in automobile and construction machinery, such as strong vibration, wailing and abnormal wear phenomenon. Aiming at this problem, the influences on gear transmission system of meshing stiffness and impact were considered, and multi-body dynamics simulation was conducted on Epicycloid hypoid gear by means of software ADAMS. Finally, the change rules of contact parameters were obtained under different driving conditions including advancing, backing, neutral backing and neutral advancing, which provides the basis for the designs of extended Epicycloid bevel gear and hypoid gear.